Effects of Family-Supported Healthcare on Children with Asthma - Shao M; Liu Z; Liu T (Dove Medical Press, 2024)
Mingyu Shao,1 Zhaohong Liu,1 Tongtong Liu2 1Department of Child Health Care, Zibo Central Hospital, Zibo, Shandong, 255020, People's Republic of China; 2Department of Pediatrics, Zibo Central Hospital, Zibo, Shandong, 255020, People's Republic of ChinaCorrespondence: Tongtong Liu, Department of Pediatrics, Zibo Central Hospital, No. 54 Gongqingtuan West Road, Zhangdian District, Zibo, Shandong, 255020, People's Republic of China, Tel +86-18560290203, Email liutongtong321@126.comIntroduction: Healthcare is essential for asthma control, however, whether family-supported healthcare improves therapeutic effects in childhood asthma remains unclear.Methods: The enrolled patients were randomly divided into control and intervention groups. The pulmonary function was evaluated by forced expiratory volume in 1 s as a percentage of forced vital capacity (FEV1/FVC) and fractional exhaled nitric oxide (FeNO). Asthma control and life quality were assessed via a childhood asthma control test and pediatric asthma quality of life questionnaire. Inflammatory cytokines interleukin-6 (IL-6) and interleukin-17 (IL-17) were determined by enzyme-linked immunosorbent assay.Results: No significant differences existed in the basic characteristics of asthma children and their parents among two groups. The increase of FEV1/FVC was higher in the intervention group versus the control group (76.47 ± 10.76% vs 69.76 ± 8.88%, p = 0.001 at the time of post-intervention), and the decrease of FeNO was greater in the intervention group (30.43 ± 6.85 bbp vs 35.64 ± 6.62 bbp, p = 0.003 at the time of post-intervention). Family-supported healthcare highly improved asthma control and quality of life in childhood asthma post-treatment. Meanwhile, the inflammatory cytokines IL-17 (118.14 ± 25.79 pg/mL in intervention group vs 142.86 ± 28.68 pg/mL in control group, p = 0.004 at the time of post-intervention) and IL-6 (103.76 ± 23.11 pg/mL in intervention group vs 119.73 ± 22.68 pg/mL in control group, p = 0.009 at the time of post-intervention) significantly decreased by family-supported healthcare intervention. Importantly, acute exacerbation (80.8% in intervention group vs 95.7% in control group, p = 0.030) and rehospitalization cases (88.5% in intervention group vs 100% in control group, p = 0.028) also decreased by family-supported healthcare intervention.Discussion: Family-supported healthcare improves pulmonary function and quality of life while alleviates inflammation, acute exacerbation, and rehospitalization in childhood asthma post-routine treatment.Keywords: asthma, family-supported healthcare, pulmonary function, IL-6, IL-17